Mechanical properties of rice husk ash as a mineral addition in concrete / Kartini Kamaruddin and Hamidah Mohd Saman - Kamaruddin, Kartini; Mohd Saman, Hamidah (Research Management Institute (RMI), 2008)
It is shown that some of the wastes have properties that would improve the quality of concrete produced. One such waste is agricultural waste rice husk, which constitutes about one-fifth of 600 million tones of rice produced annually in the world. The performance of RHA concrete was found to be varied among those of researchers and most of the studies encompassed for the utilisation of high grade concrete. This paper reported the investigation carried out on the mechanical properties of normal strength concrete of grade 30 N/mm2 with various partial replacement level of ordinary Portland cement (OPC) with Rice Husk Ash (RHA). Two(2) batches of same grade of concrete with and without use of superplasticiser (Sp) were adopted. The mechanical properties evaluated are in terms of compressive strength, flexural strength and tensile splitting strength of RHA concrete with and without superplasticiser (Sp). The results show that the optimum replacement level of RHA was 20 % and with the addition of Sp the replacement of RHA was taken as 40 %. However, the results of the study show that the performance in term of flexural strength and tensile splitting strength does not significantly improved with the replacement of cement with RHA.